E-LIBRARY PADA PERPUSTAKAAN SMK PRASASTI KARANG BERAHI KOTA JAMBI - Djauhari, Teuku; Dede, Alan (FORTECH (Journal of Information Technology), 2019)
From the background of the problems found in SMK Prasasti Karang Berahi Kota Jambi is in the application of data processing books are still relatively simple, only data processing books while data collection of borrowing and returning books are still writing / note on the agenda book for it is still many shortcomings in the application previous. To help these activities need to be created or designed a program or application that can be used together and able to handle all the activities of the library online or programmed with a good system. This E-library application is built using web technology using PHP scripting language, MySQL database, and Framework. The inputs used are library data books, member data, order data, lending and return data. Then generate output in the form of information data books, member data, data on borrowing transactions and returns in the library. With the implementation of this Web-based E-Library System at SMK Prasasti Karang Berahi so that it has an effect on the school, etc. and assist library staff in delivering library data book offline and online because of the data presented quickly.